2013
DOI: 10.2304/rcie.2013.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Academic Journals in Education: A Comparison of Publication Patterns in England and Germany

Abstract: This article outlines some of the findings of a project funded by the German Research Association which conducted an analysis of six leading journals of education in Germany and England. All articles published in these journals between 2001 and 2009 were analysed according to thematic foci, methodological approaches and characteristics of authors. The findings of this analysis demonstrate that there are clear differences and similarities in publication patters between different journals and countries and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In the German context, the use of empirical data in all the research grants in our sample may be surprising considering the more philosophical, humanities-based tradition in ER there, shown in earlier research (Dees and Botte, 2012; Schriewer and Keiner, 1992). Yet, this confirms what Ertl et al (2013, 2015) discovered in examining publication patterns in both countries. This may be explained by the increased attempts of scholars to find utilitarian answers to “what works” in education, more generally reflecting a highly instrumental science-for-development model institutionalized globally (Drori et al, 2003).…”
Section: Discussion: Er On Systems In Context or Learners In The Systemsupporting
confidence: 87%
See 2 more Smart Citations
“…In the German context, the use of empirical data in all the research grants in our sample may be surprising considering the more philosophical, humanities-based tradition in ER there, shown in earlier research (Dees and Botte, 2012; Schriewer and Keiner, 1992). Yet, this confirms what Ertl et al (2013, 2015) discovered in examining publication patterns in both countries. This may be explained by the increased attempts of scholars to find utilitarian answers to “what works” in education, more generally reflecting a highly instrumental science-for-development model institutionalized globally (Drori et al, 2003).…”
Section: Discussion: Er On Systems In Context or Learners In The Systemsupporting
confidence: 87%
“…This explains the presence of social policy and development studies disciplines as well as the international focus in 24 research grants in the UK. By contrast, German ER is dominated by learner-centered disciplines, such as education science and psychology, but far more focused on the core discipline, confirming earlier research (Dees and Botte, 2012;Ertl et al, 2013Ertl et al, , 2015Huth, 2012).…”
Section: Discussion: Er On Systems In Context or Learners In The Systemsupporting
confidence: 79%
See 1 more Smart Citation
“…Aussems et al (2011) also found that the quasi-experimental designs were not used very often in 18 social science journals that they investigated. Ertl et al (2013) compared six leading journals of education in Germany and England in the period 2001 to 2009. They found a higher proportion of non-empirical articles (often using a historical approach) in the three German journals and a higher proportion of articles drawing on primary empirical data in the three English journals.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There was a third study funded by the German Research Association which compared four leading US and four pan-European education journals. Data from this study will not be brought into the comparison in this paper, as it aims to compare national contexts and the findings have been reported on in several other papers, such as Ertl et al (2012Ertl et al ( , 2015. This paper focuses on some of the data and findings from the first German-funded project and compares those with the Australian context.…”
Section: Research Extent and Timelinesmentioning
confidence: 99%